Innovation, employment and skills in advanced and developing countries: A survey of the literature - Marco Vivarelli (Institute for the Study of Labor (IZA), 2012)
This paper critically discusses the theoretical and empirical literature on the quantitative and qualitative employment impact of technological change, compares the relative explanatory power of the competing theories, and explains in detail the macro and micro evidence on the issue, with reference both to the advanced economies and the developing countries (DCs).
urn:nbn:de:101:1-201203145587
Keywords: O33; 330; technology; innovation; employment; skill; skill-biased technological change; Innovation; Qualifikation; Technischer Fortschritt; Beschäftigungseffekt; Theorie; Industriestaaten; Entwicklungsländer